Frederick Rodgers papers - Rodgers, Frederick, 1842-1917.
Correspondence, diaries, journals, writings, reports, notebooks, legal records, printed matter, charts, maps, photographs, and other papers relating chiefly to Rodgers's naval career and family. Includes material pertaining to his service in the U.S. Navy during the Civil War and as a member of the U.S. Navy Examining and Retiring Board and president of the U.S. Navy Board of Inspection and Survey. Also documents his education at the United States Naval Academy, Annapolis, Md., and family affairs including matters relating to the family estate, Sion Hill, Havre de Grace, Md. Subjects include naval, maritime, and diplomatic affairs; the Spanish-American War, 1898; Philippine-American War, 1901-1902; Russo-Japanese War, 1904-1905; round-the-world cruise of the USS New York (Cruiser), 1901-1902; appraisal of naval vessels; condition and management of the New York Naval Shipyard and of lighthouses and ports along the Atlantic coast; Rodgers's audience with Cixi, Empress dowager of China, in 1902; and conditions in Beijing, China, following the Boxer Rebellion, 1899-1901. Family correspondents include his wife, Sarah M. Fall Rodgers, and his uncle, John Rodgers. Other correspondents include Charles H. Allen and Theodore Roosevelt.
Naval officer.
Collection material in English, French, and Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Charles H. -- 1848-1934 -- Correspondence; Cixi, -- Empress dowager of China, -- 1835-1908.; Rodgers, John, -- 1812-1882 -- Correspondence; Rodgers, Sarah M. Fall, -- approximately 1850- -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Rogers family; United States. -- Navy; United States. -- Navy -- Appointments and retirements; United States. -- Navy. -- Board of Inspection and Survey; United States. -- Navy. -- Examining and Retiring Board; New York (Cruiser); New York Naval Shipyard; United States Naval Academy; Harbors -- Atlantic Coast (U.S.); Lighthouses -- Atlantic Coast (U.S.); Russo-Japanese War, 1904-1905.; Spanish-American War, 1898 -- Naval operations; Voyages around the world; Warships -- United States; Beijing (China) -- History; China -- History -- Boxer Rebellion, 1899-1901.; Havre de Grace (Md.) -- Social life and customs; Sion Hill (Md. : Estate); Philippines -- History -- Philippine American War, 1899-1902.; United States -- Foreign relations -- 1865-1921.; United States -- History -- Civil War, 1861-1865 -- Naval operations; Rodgers family; Naval officers